Indications of Predatory Pricing on Tiktok Shop and Its Impact on MSME Actors - Afifatus Sholikhah; Edita Rachma Kamila; Laily Muzdalifah (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
There are indications of predatory pricing carried out by tiktok shop as an e-commerce. The action is practiced through flash sales, live streaming and discounts that continue to be carried out at any time. This study aims to analyse the indications of predatory pricing on tiktok shop and its impact on MSME players in Sidoardo Regency. The method used in this research is qualitative by conducting literature studies and interviews. The results showed that tiktok shop had a negative impact on MSMEs in Sidoarjo Regency.